Water Quality Monitoring System - Vishwajit V. Jade; Prathamesh P. Mandavkar; Atharv M. Nevrekar; Aditya R. Panchal; Gajanan P. Khapre (International Journal of Electrical Machine Analysis and Design, 2025)
Water contamination is a serious issue that endangers both human health and the environment. Monitoring water quality in real time is crucial to ensuring that people have access to clean and safe drinking water. This project uses Internet of Things (IoT) technologies to provide a low-cost, straightforward water quality monitoring device. The system measures the temperature, pH, turbidity (cloudiness), and water flow using a variety of sensors. These tests aid in determining whether water is suitable for human consumption. As the core controller, the ESP8266 module is the primary component of the system. Data is gathered from the sensors and processed instantly. This data is transmitted to an internet platform over Wi-Fi so that it may be watched from any location. Because of this real-time access, any changes in the quality of the water are promptly observed, enabling prompt response if problems occur. Through early detection of water pollution, this method contributes significantly to health protection. By maintaining the safety and cleanliness of water supplies, it also contributes to environmental conservation. The system can be utilized in homes, businesses, and farms due to its low cost and simplicity of setup. This water quality monitoring system makes it easier and more effective to assess the safety of the water by utilizing Internet of Things technology. It helps guarantee that everyone has access to safe water and offers precise, up-to-date statistics. This idea provides a clever and workable way to stop water contamination and encourage a more sustainable, healthy future.
Keywords: Internet of things (IoT); Microcontroller; Water quality monitoring; data platform; environmental monitor; sensors; wireless communication